Role and potentialities of bacteria associated with Tuber magnatum: A mini-review - Monaco, Pamela; Naclerio, Gino; Mello, Antonietta; Bucci, Antonio (Frontiers in Microbiology, 2022)
Among the hypogeous ectomycorrhizal fungi, the white truffle Tuber magnatum Picco is the species of greatest interest, both from an ecological and economic point of view. The increasing market demand of the precious white truffle along with the fall in its natural production led to a growing interest in cultivation techniques and encouraged truffle growers and researchers to deeper investigate factors that could affect and improve T. magnatum productivity. In this context, microbial communities play a central role. Indeed, in the last few years, the hypothesis of a potential link between microbial community composition and truffle orchard productivity is arousing a greater attention. Moreover, since the value of the prized T. magnatum can vary in relation to its provenience, the need to define a reliable tracking system is also emerging and bacteria appear to be a promising tool. Accordingly, the present mini-review summarises the knowledge currently available on T. magnatum microbial communities, focusing on the role of truffle-associated bacteria and highlighting similarities and differences between samples of different origin, to address the following issues: i) Is there a correlation between microbial taxa and truffle ground productivity? ii) Can bacteria actually be used as markers of T. magnatum geographic origin? The identification of microorganisms able to promote T. magnatum formation may represent an important advance in the field of truffle farming. Similarly, the detection of bacterial taxa that can be used as markers of T. magnatum origin could have a considerable impact on truffle industry and trade, even at local scale.